Soft tissue covers in hypospadias surgery: Is tunica vaginalis better than dartos flap? - Anjan Kumar Dhua; Satish Kumar Aggarwal; Shandip Sinha; Simmi K Ratan (Wolters Kluwer Medknow Publications, 2012)
Aim: To compare tunica vaginalis with dartos flap as soft tissue cover in primary hypospadias repair. Materials and Methods: 25 cases (age range: 12-132 months; all fresh cases) of primary hypospadias were prospectively repaired by tubularized incised plate (TIP)/TIP + graft urethroplasty using tunica vaginalis flap (TVF) as soft tissue cover to urethroplasty (group A). Their results were compared with another set (group B) of age- and anatomy-matched controls (25 patients operated during the previous 3 years) who had undergone TIP repair using dartos flap as soft tissue cover. Statistical analysis of results was done with Fischer's exact test. Results: Group A: No fistula, skin necrosis, meatal stenosis, urethral stricture. One case had partial wound dehiscence that resolved on conservative treatment with no sequelae. One case required catheter removal on 3 rd day because of severe bladder spasm. There was no testicular atrophy/ascent. Group B: 3 fistulae - all required surgery. There were three cases of superficial skin necrosis that healed spontaneously without sequel. There was no meatal stenosis/urethral stricture. The difference in fistula rate between both the groups, however, was not statistically significant (P = 0.4). Conclusion: TVF may have an edge over dartos fascia for soft tissue coverage of the neourethra.